Maltreatment history, trauma symptoms and research reactivity among adolescents in child protection services - Randall Waechter; Dilesha Kumanayaka; Colleen Angus-Yamada; Christine Wekerle; Savanah Smith; The MAP Research Team (BMC, 2019)
Abstract Objective There is a well-documented link between child maltreatment and poor health across the lifespan. This provides a strong case for ongoing research with youth involved in the child welfare system to reduce negative outcomes and support resilience while being inclusive of youth voices. However, detailed inquiries about maltreatment history and health consequences may cause re-experiencing of events and psychological distress for study participants. Data that accounts for different contexts, such as severity of maltreatment history and current trauma symptomatology, have been limited in considering the question of potential harms to youth who participate in research-especially longitudinal studies. Methods This study compared self-reported impact of research participation against maltreatment history and current post-traumatic stress symptomatology among a randomly selected group of adolescents (< 18 years old) in the child protection service (CPS) system. Results Adolescents who report more serious child maltreatment and current trauma symptom severity reported higher scores on distress questions from pre- to post-assessment participation. Critically, participants who were more negatively impacted by study involvement also reported greater benefit from study involvement. Conclusion The increase in both negative and positive impact does not shift the risk/reward ratio for participation, as risks alone do not increase for this vulnerable group of CPS involved youth. These results are consistent with previous findings from studies involving non-CPS populations and underlies the importance of empirical data to address the question of change in the risk/reward ratio and what factors might play a role in any change. This information can inform inclusion/exclusion criteria for future research with these vulnerable populations, thereby reducing the risk of distress among study participants.